Temporary ponds vegetation and dynamics:SW Portugal - Pinto-Cruz, Carla (2010)
Temporary ponds are seasonal wetland habitats subjected to extreme and unstable ecological conditions. Due to their uniqueness, some are classified as priority habitats for conservation by the European Union Habitats Directive. The coastal plain of southwest Portugal, which spans across 100 km north to south and hosts a large number of temporary ponds as a consequence of climatic and edaphic characteristics, was thus chosen as the study area. The main aim of this dissertation is to study the biology, ecology and dynamics of the plant communities of temporary ponds. Three pond types were defined, Mediterranean temporary ponds, marshlands and disturbed ponds. Within them 15 plant communities and their indicator plant species were identified, enabling clear practical recognition of these habitats. A functional plant classification is proposed in order to allow comparative ecological assessments in Mediterranean temporary ponds throughout the globe. The results confirm the importance of the hydroperiod and soil texture as driving factors of ecosystem functioning. This work emphasizes the importance of these singular habitats for conservation and gives insights for its sustainable use and possible restoration.